Reviewing School District and Caregiver Engagement: Toward Building Capacity to Serve English Learners - Howell, Emily; Kaminski, Rebecca; Pirolla, Tobi (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2024)
The authors conducted a comprehensive literature review of school district partnerships with caregivers of ELs to inform this project design. This literature review addresses the following research question: What are the needs of caregivers of ELs in K-12 schools, and how are school partnerships supporting these caregivers? This literature review will address these gaps and overcoming EL caregiver underrepresentation by discussing seven focused and three theoretical codes drawn from a comprehensive review of 21 articles. Initial findings revealed 26 initial codes. These initial codes were collapsed thematically to form six focused codes discussed in these results: defining caregiver engagement, history and context, preparation needed, implementation strategies, path forward, and impact. These six focused codes were further collapsed into past, current, and future implications.